Inquérito de suplementação nutricional e experiência no treinamento resistido entre jovens do interior e litoral paulista - Siqueira, Leandro Oliveira da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
To the practitioners of resistance exercise, a better performance is associated with nutritional habits and the help of nutritional supplements. Whatever, this use has been made improperly and without foundation, advised by persons not trained, leading to misuse. To analyze the profile of practitioners in the knowledge of and access to supplements, as well as knowledge about the sport and the need to use additional food resources. A questionnaire will be used to youths aged 15 to 21 consumers of nutritional supplements on the sports, the substance used, why the substance used, who appointed her, which substances have been used, satisfaction with that product, and socioeconomic characteristics of the individual. The data will be correlated by Pearson's correlation coefficient. It is expected that the abuse of supplements is associated with ease by socioeconomic status and experience in the sport for the little progress with the adoption of a routine training exercise in the circumstances only. The major difference compared to the goal of practice, was the motivation for the improvement of physical fitness (Guaruja 21% and Bauru 9.6%), with the intention of increasing muscle mass response occurring closer (Guaruja 22% and Bauru 19.2%) among respondents, and reported more emphasis on the Interior Health (17.3%). The use of supplements is somewhat similar to trends involving body aesthetics and fitness for participation in sports, in the Coast (hypertrophy: 33% body fat reduction, improved endurance and improved performance in sports: 20%), and beauty, fitness and health, the Interior (hypertrophy: 41% increase in strength: 22%, and quality of life: 15%). Interest in the use of supplements is mostly aimed at the improvement of overload training (Guaruja 67% and Bauru 56%) but the sources of information on the use of supplements have become more secure among the respondents of the Interior (gym teacher: 20%, Conferences and Symposia: 12%, and the...

Para os praticantes de exercício resistido, um melhor rendimento está associado aos hábitos nutricionais e o auxilio de suplementos nutricionais. Porém esse uso tem-se dado de forma abusiva e sem fundamento, aconselhados por pessoas não capacitadas, levando ao uso indevido. Analisar o perfil dos praticantes quanto ao conhecimento e forma de acesso aos suplementos, bem como quanto ao conhecimento sobre a modalidade e a necessidade de uso de recursos nutricionais suplementar. Será aplicado um questionário aos jovens de 15 a 21 anos consumidores de suplementos nutricionais sobre a prática esportiva, a substância utilizada, o porquê da substancia utilizada, quem a indicou, quais substâncias já foram utilizadas, a satisfação com tal produto, e as características socioeconômicas do indivíduo. Os dados serão correlacionados pelo coeficiente de Pearson. Espera-se que o abuso dos suplementos esteja associado à facilidade pelo nível sócio-econômico e à experiência na modalidade pela pouca evolução com a adoção de uma rotina de treinamento circunstanciada apenas nos exercícios. A maior diferença, em relação ao objetivo da prática, foi a motivação pela melhora do condicionamento físico (Guarujá 21% e Bauru 9,6%), sendo a intenção de aumento da massa muscular a resposta com ocorrência mais próxima (Guarujá 22% e Bauru 19,2%) entre os entrevistados, e a ênfase na saúde mais relatada no Interior (17,3%). O uso de suplementos ocorre com tendências pouco semelhantes, envolvendo a estética corporal e à aptidão para participação em esportes, no Litoral (hipertrofia: 33%; redução de gordura corporal, melhora na resistência física e melhora no rendimento esportivo: 20%), e estética, aptidão e saúde, no Interior (hipertrofia: 41%; aumento de força: 22%; e qualidade de vida: 15%). O interesse pelo uso de suplementos é majoritariamente voltado ao aprimoramento da sobrecarga de treinamento (Guarujá 67% e Bauru 56%)
Keywords: Jovens - Conduta; Treinamento (Atletismo); Suplementos dieteticos; Massa muscular; Young adults Conduct of life